2022
DOI: 10.1332/251510821x16423796696763
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for and perceptions about politicians’ goals and how they impact women’s and men’s political ambition

Abstract: Women consistently report lower levels of nascent political ambition than men, which causes problems for the recruitment of women in politics. The aim of this study is to better understand the mechanisms behind this gender gap by simultaneously studying the extent to which gender differences in preferences for and perceptions about the typical goals attained through a political career (power, independence and communal goals) can explain gender differences in political ambition. Using data collected among Belgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A necessary prerequisite to aspire to a political office is at least some level of (nascent) political ambition, and research consistently finds a clear and strong gender gap in political ambition: women tend to have lower levels of such ambition than men (Allen & Cutts, 2020;Coffé et al, 2022;Dahl & Nyrup, 2021;Kanthak & Woon, 2015;Lawless & Fox, 2010). As rational actors, women, just like men, consider whether the circumstances are conducive to their entry in politics.…”
Section: Gender and Political Ambition On Different Levels Of Policy ...mentioning
confidence: 99%
See 2 more Smart Citations
“…A necessary prerequisite to aspire to a political office is at least some level of (nascent) political ambition, and research consistently finds a clear and strong gender gap in political ambition: women tend to have lower levels of such ambition than men (Allen & Cutts, 2020;Coffé et al, 2022;Dahl & Nyrup, 2021;Kanthak & Woon, 2015;Lawless & Fox, 2010). As rational actors, women, just like men, consider whether the circumstances are conducive to their entry in politics.…”
Section: Gender and Political Ambition On Different Levels Of Policy ...mentioning
confidence: 99%
“…Nascent political ambition indicates the intention to run for office without reference to a particular candidacy for a specific election and is a necessary condition for expressed ambition (Bernhard, Shames, & Teele, 2021). Research has consistently shown that women have lower levels of nascent political ambition than men (Allen & Cutts, 2020;Coffé, Devroe, Vandeleene, & Wauters, 2022;Dahl & Nyrup, 2021;Kanthak & Woon, 2015;Lawless & Fox, 2010), which causes problems for the recruitment of women for a political mandate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation